Antitumor immunostimulatory activity of polysaccharides from Salvia chinensis Benth. (20th June 2015) - Shu, Guangwen; Zhao, Wenhao; Yue, Ling; Su, Hanwen; Xiang, Meixian
Abstract: Ethnopharmacological relevance: Salvia chinensis Benth ( S. chinensis ) is a traditional herb applied in the treatment of hepatocellular carcinoma (HCC). Polysaccharides abundantly exist in this plant. However, it remains poorly understood if polysaccharides from S. chinensis (PSSC) contribute to its anti-HCC activity. Materials and methods: The in vivo anti-HCC activity of PSSC was evaluated in Kunming mice bearing H22 ascitic hepatoma cells. An array of physiological indexes was measured to evaluate toxicological effects on host animals. Subgroups of immune cells were purified by a magnetic-activated cell sorting system and analyzed by flow cytometry. Reverse transcription real-time PCR and immunoblotting were recruited to determine the effects of PSSC on the cellular signaling of different subgroup of immune cells. Results: PSSC suppressed in vivo proliferation of H22 cells with undetectable toxic effects on tumor-bearing mice. PSSC alleviated tumor transplantation-induced CD4+ T cell apoptosis and dysregulation of serum cytokine profiles, which elevated cytotoxic activities of natural killer and CD8+ T cells. PSSC reduced serum levels of prostaglandin E2 (PGE2). Injection of exogenous PGE2 completely abrogated the antitumor immunostimulatory activity of PSSC. Cyclic adenosine monophosphate (cAMP) is the second messager of PGE2. In CD4+ T cells, PSSC substantially declined intracellular cAMP. This event elevated protein levels of JAK3, enhancing STAT5 phosphorylation and STAT5-depedent expression of anti-apoptotic genes. Cyclooxygenase-2 is the key enzyme mediating biosynthesis of PGE2. PSSC suppressed the transcription and translation of cyclooxygenase-2 in tumor associated macrophages. Conclusion: Our data clearly showed antitumor immunostimulatory activity of PSSC against transplanted H22 HCC cells. Suppressing tumor transplantation-induced PGE2 production was implicated in the anti-tumor immunostimulatory activity of PSSC. These works provides novel insights into the traditional application of S. chinensis against HCC and supported considering PSSC as an adjuvant reagent in clinical HCC treatment. Graphical abstract: